(untitled) (Práxis Educativa, 2023)
This article analyzes the divergences and convergences on the treatment of research data and the investigative field of Human and Social Sciences, in Resolution no. 466/2012, in Resolution no. 510/2016 and the General Data Protection Law (LGPD). This is a documentary investigation, with a qualitative approach and exploratory objective, based on the understanding of the theorists De La Fare, Carvalho and Pereira (2017), Mainardes (2017) and Peixoto (2017). The results indicate: i) the lack of determinants linked to human integrity; ii) the lack of autonomy of the research subject; iii) the need to modernize data processing resolutions; iv) the need for the researched subject to access the investigation results, as well as the transparency of access to his/her data; v) the need to fertilize teaching and an ethical culture in educational institutions. Keywords: Ethics in Research. Human and Social Sciences. Procedures.